Stridulation songs of some Tettigoniidae (Ensifera, Orthoptera) from Papua New Guinea - Morris, Glenn K; Ingrisch, Sigfrid; Willemse, Fer; Willemse, Luc; Luca, Paul A. De; Klimas, Dita (Zootaxa, 2025)
Frequency-domain power spectra and time-domain wave amplitude patterns of stridulation signals, are presented for 20 tettigonioid taxa from Papua New Guinea (PNG). Songs of 13 extant species accompany those of 7 species new to science. Extant are Acauloplacella immunis (Phyllomimini), Eumecopoda cyrtoscelis, Segestidea novaeguineae (Mecopodinae), Salomona ustulata, Philmontoides wau, Parahabetia pictifrons, Glennagraecia curvata, Trichophallus capillatus, Morocera nigrifrons, Pseudorhynchus cornutus, Conocephalus semivittatus semivittatus (Conocephalinae), Hexacentrus mundus (Hexacentrinae) and Phyllophora lanceolata (Phyllophorinae). New taxa being described include the species Paraphyllomimus pipiens sp. nov., the subspecies Paraphyllomimus buergersi wauensis, (Phyllomimini), also the subspecies Charisoma karschi ‘goggle eye’, Eumecopoda pumila, Rentziella gen. nov., Rentziella rufa, Rentziella ‘big blue’(Mecopodinae) and Salomona ‘darth’ (Conocephalinae). The term ‘strigin’ is suggested as an effective way to refer to the organ of ensiferan sound generation. From waveforms of the sounds and from strigin morphology at least three kinds of stridulation can be inferred: transient, resonant and elastic uncoupled. The resonant-stridulating species Acauloplacella immunis presents an exceedingly high-Q10 value of 45 for its lone 8.8 kHz spectral peak. The 2 species of Eumecopoda frequency modulate (FM) sinusoids in the audio frequency range. The strigins of many species of Mecopodinae incorporate a modified anal vein, the overmirror fold (OF), that cantilevers out above the mirror (speculum) and partially occludes its dorsal aspect: the form of this OF and possible acoustic function are discussed. Old World Phyllomimini contrast a dorsoventral leaf mimicry with a laterally compressed sagittal leaf mimicry seen in New World Pterochrozini and species of both tribes seem to favour very high-Q audio carriers. Defensive sternocoxal stridulation by a phyllophorine katydid has a broad band ‘noisy’ spectrum.